Coronavirus Pandemic in Georgia: Between Church and Vaccination - S. B. Manyshev (Международная аналитика)
The article is devoted to the issues of preventing the novel coronavirus infection in Georgia during the pandemic and the influence of the religious judgments of the Georgian Orthodox Church on them. Based on data from open sources the article describes the state of the healthcare system in Georgia during the coronavirus pandemic. A retrospective analysis of the reform of the country’s healthcare system in the post-Soviet period was performed, shedding light on its readiness for significant challenges, such as the pandemic. Thereby the reasons for the population’s distrust of the public healthcare system in general and the preventive measures it offers in the form of vaccination become clear. Much attention is paid to the relationship between the state and the church, as well as their attitude to the issues of preventing infection through vaccination and influencing public opinion. A set of measures taken by the government to localize the infection, aimed at preventing its further spread, is analyzed. Against the background of a description of the attitude of the clergy to the coronavirus pandemic in other countries, both the main position of the Georgian Orthodox Church regarding the disease and preventive measures, as well as the views of individual hierarchs, which do not always coincide with the official opinion of the Synod, are demonstrated. In addition, the author illustrates the history of the protest movement in Georgia during the pandemic, associated with state policy regarding measures to prevent the novel coronavirus infection. Separately, information is presented from the author’s field material obtained from informants during the pandemic, demonstrating different views on the issues of observance of religious rituals during the pandemic, trust in the healthcare system, and vaccination as a preventive measure supported by the state. In conclusion, the consequences about the issues posed by the coronavirus pandemic to the Georgian government are demonstrated, such as the availability and quality of medical care, as well as the interaction of the institutions of the secular state and the Georgian Orthodox Church.